(NtADVIKSKAQ SIMFONI^ESKAQ MUZYKAs - (Nl(B.(Na(B.(NnAZAROWAs ((NdU[ANBEs (NdONI[s, 1986)
(NoSNOWNAQ ZADA^A DANNOJ MONOGRAFII(B-(NANALIZ ISTORI^ESKOGO PROCESSA STANOWLENIQ I SIMFONI^ESKOGO MUZYKI(B.s
Keywords: (NISTORIQs